Use of IAEA's phase-space files for the implementation of a clinical accelerator virtual source model - Rucci, José Alexis (2013)
In the present work, phase-space data files (phsp) provided by the International Atomic Energy Agency (IAEA) for different accelerators were used in order to develop a Virtual Source Model (VSM) for clinical photon beams. Spectral energy distributions extracted from supplied phsp files were used to define the radiation pattern of a virtual extended source in a hybrid model which is completed with a virtual diaphragm used to simulate both electron contamination and the shape of the penumbra region. This simple virtual model was used as the radiation source for dosimetry calculations in a water phantom. The proposed model proved easy to build and test, and good agreement with clinical accelerators dosimetry measurements were obtained for different field sizes. Our results suggest this simple method could be useful for treatment planning systems (TPS) verification purposes.